Figurative Language Found In Olivia Rodrigo’s Album “Guts” - Hilwa Sabrina; I Komang Sumaryana Putra; Ni Made Suwari Antari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This study aimed to identify the type and analyze the meaning of figurative language in the “Guts” album song lyrics. The data were obtained from 12 songs entitled: “All-American Bitch”, “Bad Idea Right?”, “Vampire”, “Lacy”, “Ballad of a Homeschooled Girl”, “Making the Bed”, “Logical”, “Get Him Back!”, “Love is Embarrassing”, “The Grudge”, “Pretty isn’t Pretty”, and “Teenage Dream”. This study used a descriptive qualitative method. This study used the theory of types of figurative language from Abrams and Harpham (2015) and the theory from Leech (1981) to analyze the meaning of figurative language. Out of the 14 types of figurative language, the writer only found seven types of figurative language, namely, simile, metaphor, hyperbole, kenning, paradox, irony, and aporia. They were followed by some meanings, which were connotative and affective.